A Descriptive Study on the Prevalence of Squamous Cell Carcinoma of Head and Neck - Ajab Noor Khan, Ali Nawab (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the risk factors and the sites involved so as to promote the education in the community and improve the Treatment besides prevention of the disease. The mean age of patients enrolled in the study is 52±8.31 years and the percentage of the males is higher as compared the females i.e 57% of patients were males while 43% females. And among the patients 69% belonged to city areas and 31% were from rural community. Material and Methods: The design of this study was Descriptive study. This study was conducted at Mardan medical complex, Mardan and the duration of this study was from July 2020 to May 2021. 100 patients were enrolled in the study and Biopsies were taken and then sent to the laboratory for histopathology. Disease primarily of the region, mucosal disease. Children with congenital tumors, mentally retarded cases. Conclusion: The squamous cell carcinoma is a major problem due to its high morbidity and mortality. And it is the most common malignancy of head and neck region. The most common area involved is hypo-pharyngeal area